PARTISIPASI PETANI DALAM KEGIATAN PENYULUHAN DAN ADOPSI PEMUPUKAN PADI SAWAH DI KECAMATAN KERSAMANAH KABUPATEN GARUT - Chicka Anggita Putri; Oeng Anwarudin; Dwiwanti Sulistyowati (JURNAL AGRIBISNIS TERPADU, 2019)
The increase in paddy rice production has been carried out by the government with the implementation of technological innovation through extension activities involving farmer participation. This study aims to analyze descriptively the participation of farmers in extension activities and adoption of rice fertilization and analyze the factors associated with farmer participation in extension activities and adoption of rice paddy fertilization. The study was conducted in Kersamanah, Garut. The sample of the study was 87 rice farmers taken by Cluster Random Sampling technique. Independent variables include the characteristics of farmers, extension activities and farmer participation in extension activities and the dependent variable is the adoption of rice fertilization. The analysis technique used is descriptive analysis and Rank Spearman correlation analysis. The results showed that farmer participation in extension activities was classified as low. The adoption of farmers includes a high level of knowledge, the attitude of farmers is moderate and the skills of farmers are classified as moderate. Factors related to farmer participation in extension activities are land area, family dependents and extension activities. Factors related to farmers' knowledge are the length of farming and land area. The attitude of farmers is related to extension activities and farmer participation in extension activities. Farmers' skills are related to land area.